Manajemen Kerjasama dengan Dunia Usaha dan Dunia Industri Pada Sekolah Unggul SMK Negeri 1 Martapura dan SMK Negeri 1 Banjarbaru - Saidah, Siti; Hermina, Dina (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study aims to identify and analyze the management of cooperation between leading vocational high schools (SMK) and the business and industrial world (DUDI) at SMK Negeri 1 Martapura and SMK Negeri 1 Banjarbaru. The research method used is qualitative descriptive with a case study approach. Data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that both schools have implemented various cooperation strategies with DUDI, including student internships, joint curriculum development, and the provision of training facilities that meet industry standards. The success of this cooperation management is supported by factors such as effective communication, mutual commitment between schools and industry partners, and support from the local government. This study concludes that good cooperation between vocational schools and DUDI is crucial in enhancing students' competencies and job readiness after graduation. Recommendations are provided to strengthen the synergy between education and industry through improved training programs for teachers and the refinement of cooperation evaluation mechanisms.